A critical history of architectural modernism - Buras, Nir H.; Katona, Vilmos; Mehaffy, Michael W.; Salingaros, Nikos A. (Journal of Architecture and Urbanism, 2025)
Future generations deserve and need an honest accounting of architectural Modernism, and its Neo-Modernist and “Post-Modernist” variants, based on scientific analysis and the factual historical record. Reintroducing traditional tectonic culture and focusing on applying fractal and planar symmetries to design critique provides a more revolutionary account of the Modernist concept, its associated “propaganda”, and the physical legacy of the movement. The authors seek answers to two questions: (1) whether Modernist architecture justly conquered the world by its claimed “Zeitgeist” – or was its success due to other factors; and (2) to what extent Modernism brings about the originally promised cultural and social benefits today. This essay seeks to clear up the ambiguity of the Modernist architectural doctrine through facts, and includes criticisms regarding its massive detrimental impact on the world’s built and natural environments. A growing movement in Europe and elsewhere is challenging the legitimacy of many contemporary architectural designs. These critics attack the persistence of discredited Modernist theory, and the resulting harm to people and our planet. Defenders respond that the members of this movement are ignorant populists who do not understand the legitimate theoretical and cultural foundations of contemporary design. Here we examine this controversy and conclude that a considerable body of scientific evidence supports the critics. By focusing on the choices we do have today, we empower architects to implement drastic changes in new projects.